INFLUENCE OF SITTING ORIENTATION ON UPPER EXTREMITY FUNCTION IN NORMAL CHILDREN BETWEEN 5 TO 16 YEARS USING NINE HOLE PEG TEST - K, Misal Amruta; Chetana, Kunde; S, Ganvir Suvarna (International Journal of Clinical and Biomedical Research, 2018)
Background: This study was to measure the upper extremity performance time on Nine Hole Peg Test in two different sitting orientations relative to vertical plane. Aim: To find out the influence of sitting orientation on upper extremity motor function using NHPT. Methods: 100 children with the mean age 11year (53 male, 47 female) participated in the study. Children were selected according to inclusion and exclusion criteria. Age groups were re-established for data representation purposes as: 5-7, 8-10, 11-13, 14-16. Each one was briefly interviewed prior to the test, procedure explained and statistical analysis was done for the final results. Results: Gender wise relation revealed non-significant difference in performance time on NHPT in 90o upright and 15o anterior sitting orientation. Performance time on NHPT with dominant and non-dominant hand in 90o upright & 15o anterior sitting orientation shows significant difference. The mean performance time with dominant hand on NHPT was slightly lesser in 15o anterior sitting orientation than 90o upright orientations. According to age wise distribution the performance time on NHPT reveals that as the age increases the performance time decreases from 5-11 year. The performance time becomes constant from 11-16 years of age. Conclusion: Result of this study suggest that trunk orientation does not affect upper extremity performance on NHPT. As it implies that 15o anterior trunk orientation is equivalent to upright sitting orientation. Hence both the trunk orientation can be used to train patients for upper extremity hand function.